Geographies of aquaculture for rural development, mangrove conversions, and women identities in Infanta, Quezon - Katigbak, Evangeline O. (2008)
The fishery sector in the Philippines occupies a vital role in the economy, providing substantial employment and income; contributing export earnings; and meeting local demand for the protein requirement of the people (ADB, 2005; Lopez, 2006). Among its sub-sectors, aquaculture has been identified as one of the major sources of jobs in the rural areas in the coming years. The projected growth in aquaculture is seen to likewise support food security programs in the country's a drive towards economic development. The Philippine government continually encourages aquaculture production in different areas of the country. This is in response to food security challenges at the present and in the future, and also because growth in the sector is seen to increase export gains in the country. This study provides a deeper analysis on how aquaculture development, which has largely been driven by the international demands for seafoods, has impacted the livelihoods of coastal dwellers in the Philippines. The study captures local communities' responses to this initiative as seen in the experiences of the people of Infanta, Quezon. It details the assertion of local peoples of their rights over mangrove areas, which are common property resource, against more economically and politically powerful fishpond developers who are not even from the municipality. The study hopes to add further to the understanding of how conversion of mangrove areas to fishponds is transforming livelihoods and identities of local peoples especially the women members of the local community. This research employs the feminist political ecology in locating the ecological transformations and the consequent changes in livelihoods and identifies of the local population in Infanta.